If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(e + -8) + 12 + -2e = 0 Reorder the terms: 7(-8 + e) + 12 + -2e = 0 (-8 * 7 + e * 7) + 12 + -2e = 0 (-56 + 7e) + 12 + -2e = 0 Reorder the terms: -56 + 12 + 7e + -2e = 0 Combine like terms: -56 + 12 = -44 -44 + 7e + -2e = 0 Combine like terms: 7e + -2e = 5e -44 + 5e = 0 Solving -44 + 5e = 0 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + 5e = 0 + 44 Combine like terms: -44 + 44 = 0 0 + 5e = 0 + 44 5e = 0 + 44 Combine like terms: 0 + 44 = 44 5e = 44 Divide each side by '5'. e = 8.8 Simplifying e = 8.8
| x^2-14xy+49y^2= | | 3+2x/2+8=5x+1/5 | | -10-3=x | | 11AX-6AX+4XY+3AX= | | 5y+4=2 | | 1399=16x^2 | | 8(x+2)=24 | | 2=7x-4 | | 17n=3+16n | | 27+2(f-19)=0 | | 2+(12y+15)=y-(5y-31) | | -.8(.2n+.6)=-.32 | | 21-7k=-6k | | x^2+20x=-4 | | 8x+13y=4 | | .75a+3=7 | | ln(x+1)-ln(x)=ln(4) | | (3.2m+1.8)-1.07m=0 | | 8+3v=-6(v+8)+4v | | -5z=13-6z | | 30-5x=4x+20 | | -(3z+4)=6x-3(3z+2) | | x-2.6=-8.4 | | 10u-84=3u | | 8(k-9)=0 | | 14x-14x+(-7y+7y)=21-21 | | 11u-96=3u | | 6(2x+4)=2(4x-2) | | 5(y-2)=30 | | 1/2+2(r-5/2)=5/6 | | 4-3x=-22 | | y=2t^2-4t-1 |